A Korean Patient With Leber Congenital Amaurosis and a Homozygous RPE65 Variant Originating From a Paternal Uniparental Isodisomy - Hane Lee; Dongseok Moon; Rin Khang; Go Hun Seo; Chang Ki Yoon; Un Chul Park; Kyu Hyung Park; Eun Kyoung Lee (Molecular Genetics & Genomic Medicine)
ABSTRACT Background Leber congenital amaurosis (LCA), the most severe form of inherited retinal dystrophy, is a rare, heterogeneous, genetic eye disease associated with severe congenital visual impairment. RPE65, one of the causative genes for LCA, encodes retinoid isomerohydrolase, an enzyme that plays a critical role in regenerating visual pigment in photoreceptor cells. Methods Exome sequencing (ES) was performed on a patient with suspected LCA. Results Here, we report a 33‐year‐old male patient diagnosed with RPE65‐related LCA caused by uniparental isodisomy (UPiD) who received gene therapy as treatment, fourth patient to receive it in Korea. His fundus examinations showed salt‐and‐pepper retinal dystrophy, with diffuse extinguished signal on fundus autofluorescence and attenuated amplitude on electroretinogram. A homozygous frameshift variant NM_000329.3:c.1067del (p.Asn356MetfsTer17) in RPE65 was identified by ES with the entire chromosome 1 proving to be paternal UPiD. Within 5 months after the molecular diagnosis, the patient was treated with subretinal voretigene neparvovec (VN) therapy and is being followed up for prognosis. Conclusions To our knowledge, this patient is the first UPiD case to receive VN treatment. Performing ES as a first‐tier test was favourable because it allowed to identify UPiD that needed to be detected in addition to the disease‐causing variant.